Perkebunan Kelapa Sawit PT AMP Plantation Jorong Tapian Kandis Kabupaten Agam (Produksi dan Pengaruh Terhadap Sosial-Ekonomi Masyarakat Kecamatan Ampek Nagari 1992-2018) - Widya Sari; Hendra Naldi (Jurusan Sejarah FIS UNP, 2020)
The research contains the development of oil palm plantation production of PT AMP Plantation, Palembayan District, Agam Regency. This study uses a historical method which consists of four stages. first stage heuristic (data collection), second stage source criticism (revealing the truth of the source content), third stage interpretation (interpretation related to historical facts that have gone through source criticism stage, fourth stage historiography (history writing) .This study shows a development of coconut plantations palm oil is growing every year.The company was established in 1992 in Jorong Tapian Kandis, Palembayan District, Agam Regency.The production produced in the form of Fresh Fruit Bunches (TBS) and Crude Palm Oil (CPO), but the scope of business managed in the company is Fresh Fruit Bunches (TBS) The company provides a variety of facilities for employees in both social and economic forms such as benefits, health, education, shelter, public transportation and working equipment for employee safety and security. around and affect social life community economy.